Tumor in tumor: Metastasis of breast carcinoma to intracranial meningioma - (:unkn) unknown (PENSIERO SCIENTIFICO EDITOR, 2001)
This report presents magnetic resonance imaging (MRI) findings of a breast carcinoma metastasis in an intracranial meningioma with correlated pathological findings. MRI showed multiple foci of intense enhancement with hypointense surrounding areas. The described foci appeared to be metastatic disease from the patient's known breast carcinoma. In addition, this is the first study reported in the literature to have investigated the expression of a possibly common carcinogenic molecule in breast carcinoma metastatic to a coexisting meningioma: overexpressed c-myc oncogene was found both in the breast carcinoma compartment and in the meningioma component of the tumor.
Keywords: breast carcinoma; meningioma; metastasis; CANCER; ASSOCIATION; EXPRESSION; FEATURES